2020
DOI: 10.21873/invivo.12095
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Lesions Referred For Surgical Procedures: Single-Center 5-year Experience in Southwestern Poland

Abstract: Background/Aim: The head is a body site with a particular predisposition to skin malignancies due to exposure to UV radiation. The aim of the study was to better elucidate the characteristics of skin lesions that develop on the scalp. Patients and Methods: A retrospective review of all excised and histologically assessed lesions of the scalp at a single dermatosurgery unit throughout a fiveyear period was performed. Demographic features and lesion characteristics were compiled and analyzed. Results: Among 5,60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The most common histology in this study was SCC, followed by sarcoma. Melanoma is one of the most commonly detected scalp malignancies in Western populations, but none was seen in this study group [ 8 , 9 ]. We found that scalp tumours are more common in middle-aged adults than in older people, according to Western literature [ 7 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most common histology in this study was SCC, followed by sarcoma. Melanoma is one of the most commonly detected scalp malignancies in Western populations, but none was seen in this study group [ 8 , 9 ]. We found that scalp tumours are more common in middle-aged adults than in older people, according to Western literature [ 7 ].…”
Section: Discussionmentioning
confidence: 95%
“…The most common malignancies in Western populations are cutaneous malignancies, particularly BCC and SCC [ 2 , 7 , 8 ]. The most common histology in this study was SCC, followed by sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies explained the male predominance of scalp BCC with a higher incidence of androgenetic alopecia among males 14 , 19 . According to the recent study conducted by Chlebicka et al, skin lesions on the scalp including BCC mainly occurred in the frontal, temporal, and apex area of the scalp in Caucasian population, which are the commonly affected areas by androgenetic alopecia 20 . Thus, a lower prevalence of androgenetic alopecia among Korean males compared with Caucasians might also partially explain this result 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BCC is usually the most frequent type of scalp cancer in epidemiological analysis. 2 The main risk factors for the development of BCC include chronic sun exposure, radiation therapy, and immunosuppression. So far, the relationship between the use of hair dye and the presence of BCC has not been proven; however, many of aromatic amide derivates contained in these products are known to have mutagenic effect.…”
Section: Dyed Basal Cell Carcinoma: a Peculiar Clinical And Histopath...mentioning
confidence: 99%